The Evolution of Ronald Dworkin's Legal Philosophy: From Interpretivism to Integrity - Asa, Agam Ibnu (Centre for Literary and Cultural Studies, 2025)
Ronald Dworkin's legal philosophy marked a paradigm shift from positivism, emphasizing law as a deep interpretive practice. The problem addressed is the lack of systematic exploration into the evolution of Dworkin's thought from early interpretivism to integrity and the unity of value as a single narrative. This study aims to trace how Dworkin's ideas developed and shaped each other. Through literature review and conceptual analysis of his major works, this research finds that Dworkin's early interpretivism, which focused on criticizing Hart and the role of principles in